A phase 1 antigen dose escalation trial to evaluate safety, tolerability and immunogenicity of the leprosy vaccine candidate LepVax (LEP-F1 + GLA–SE) in healthy adults. Issue 7 (11th February 2020) - Duthie, Malcolm S.; Frevol, Aude; Day, Tracey; Coler, Rhea N.; Vergara, Julie; Rolf, Tom; Sagawa, Zachary K.; Marie Beckmann, Anna; Casper, Corey; Reed, Steven G.
Highlights: First in human evaluaiton of a defined subunit vaccine for leprosy. LepVax (LEP-F1 + GLA-SE) demonstrated to be safe. Comprable immune responses induced by 2 and 10 μg LEP-F1 protein within the vaccine. Abstract: Healthy United States-based adult volunteers with no history of travel to leprosy-endemic countries were enrolled for the first-in-human evaluation of LepVax (LEP-F1 + GLA-SE). In total 24 volunteers participated in an open-label clinical trial, with 21 receiving three injections of LepVax consisting of either 2 µg or 10 µg recombinant polyprotein LEP-F1 mixed with 5 µg of the GLA-SE adjuvant formulation. LepVax doses were provided by intramuscular injection on Days 0, 28, and 56, and safety was evaluated for one year following the final injection. LepVax was safe and well tolerated at both antigen doses. Immunological analyses indicated that similar LEP-F1-specific antibody and Th1 cytokine secretion (IFN-γ, IL-2, TNF) were induced by each of the antigen doses evaluated within LepVax. This clinical trial of the first defined vaccine candidate for leprosy demonstrates that LepVax is safe and immunogenic in healthy subjects and supports its advancement to testing in leprosy-endemic regions.